Netnography and design thinking: development and illustration in the vegan food industry. (11th February 2021) - Ashman, Rachel; Patterson, Anthony; Kozinets, Robert V.
Abstract : Purpose: This paper aims to strengthen the process of design thinking by aligning it with netnography, specifically auto-netnography, which this paper asserts is particularly suited to the task of studying and enriching the actions of "designerly types" who seek to fashion monetisable businesses. Design/methodology/approach: This paper conducts an auto-netnography with a structure divined from established design thinking theory – that of empathising, defining, ideating, prototyping and testing – to afford an understanding of how a popular health food influencer designs a successful vegan restaurant. Findings: This paper illustrates the empathetic relationship between a long-term audience member and an entrepreneur/designer/marketer. The intimate cultural analysis reveals the nature of their symbiotic entwinement. In a way that few other methods could, the method shows how this sense of reciprocity, deepens over time. Research limitations/implications: Conducting an auto-netnography is a prolonged and difficult task. Nonetheless, by revealing the rituals, expectations, roles and routines of content creators, designers and followers, this paper illustrates exciting possibilities for the enactment and development of design thinking in the marketing field. Practical implications: Designerly types such as marketers and content creators should closely study, listen to and interact with consumers by using a similarly staged process that draws equally from design thinking and auto-netnography. Originality/value: Prior to this study, existing research has not previously linked design thinking with either netnographic or auto-netnographic research.